Tinjauan Yuridis Tentang Perjanjian Sewa-Menyewa Rumah Menurut Kitab Undang-Undang Hukum Perdata Studi Kasus: Putusan Pengadilan Negeri Jakarta Utara Nomor 177/Pdt.G/2019 - Hidayat, Nashiffa Thuraya; Ardiansyah, Ardiansyah (HUMANIORUM, 2025)
The lease agreement regulates the relationship between the tenant and the landlord in accordance with the Civil Code (KUHPerdata) and becomes the legal basis for both parties. The obligations of the relevant parties regarding the lease agreement are listed in the Civil Code. Lease is defined as an agreement in which one party gives the benefit of an item to another party for a certain payment. This agreement is valid if it meets the requirements in Article 1320 of the Civil Code, including agreement, capacity, specific object, and lawful cause. Written agreements provide more certainty and legal protection than oral agreements. The obligations of the landlord and tenant are regulated in Articles 1550 and 1560 of the Civil Code, which include delivery of goods, maintenance, and responsibility for damage. In the event of default, dispute resolution can be carried out through negotiation, civil lawsuit, or cancellation of the agreement in accordance with the Civil Code. The effectiveness of security seizure is important in ensuring the fulfillment of obligations by the party owed and preventing actions that can harm the owner or tenant. In addition, a verdict of verstek can be a solution for parties who do not attend the trial, thus providing legal certainty for the injured party. By understanding this rule, it is hoped that the parties can implement the lease agreement better and minimize disputes that may arise.